Half-threaded holes markedly increase the fatigue life of locking plates without compromising screw stability. Issue 10 (5th October 2020) - Chao, Ching-Kong; Chen, You-Lin; Lin, Jinn
Abstract : Aims: To determine whether half-threaded screw holes in a new titanium locking plate design can substantially decrease the notch effects of the threads and increase the plate fatigue life. Methods: Three types (I to III) of titanium locking plates were fabricated to simulate plates used in the femur, tibia, and forearm. Two copies of each were fabricated using full- and half-threaded screw holes (called A and B, respectively). The mechanical strengths of the plates were evaluated according to the American Society for Testing and Materials (ASTM) F382-14, and the screw stability was assessed by measuring the screw removal torque and bending strength. Results: The B plates had fatigue lives 11- to 16-times higher than those of the A plates. Before cyclic loading, the screw removal torques were all higher than the insertion torques. However, after cyclic loading, the removal torques were similar to or slightly lower than the insertion torques (0% to 17.3%), although those of the B plates were higher than those of the A plates for all except the type III plates (101%, 109.8%, and 93.8% for types I, II, and III, respectively). The bending strengths of the screws were not significantly different between the A and B plates for any of the types. Conclusion: Removing half of the threads from the screw holes markedly increased the fatigue life of the locking plates while preserving the tightness of the screw heads and the bending strength of the locking screws. However, future work is necessary to determine the relationship between the notch sensitivity properties and titanium plate design. Cite this article: Bone Joint Res 2020;9(10):645–652.